2021
DOI: 10.1111/fwb.13703
|View full text |Cite
|
Sign up to set email alerts
|

Variation of stomach content and isotopic niche of puye Galaxias maculatus (Jenyns, 1842) in large river systems of southern Chile

Abstract: Understanding of trophic structure and flow of energy within river systems is essential for informed management of these ecosystems and conservation of native fish fauna and fisheries resources. Food resources used by riverine fish depend on productivity within the main stem and adjacent floodplains, terrestrial inputs, and longitudinal and lateral hydrologic connectivity. Trophic ecology of puye (Galaxias maculatus Jenyns, 1842) in Chilean river systems remains poorly understood and studies that combine short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
3
2
0
Order By: Relevance
“…In the Bueno and Valdivia rivers, a significant proportion of the fish captured reported continuous movement between the upper and middle sections of each river system, with maximum detected displacement of 64 km (Bueno River) and 72 km (Valdivia River). This movement pattern corroborates recent findings of similar resource use and significant overlap of isotopic niche spaces of puye in upper and middle sections of both Valdivia and Bueno rivers 20 . Predictive analyses did not associate any of the fish captured in Valdivia and Bueno river systems with estuarine elemental signatures suggesting restriction of their life-histories to freshwater habitats possibly distinct from estuarine populations.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the Bueno and Valdivia rivers, a significant proportion of the fish captured reported continuous movement between the upper and middle sections of each river system, with maximum detected displacement of 64 km (Bueno River) and 72 km (Valdivia River). This movement pattern corroborates recent findings of similar resource use and significant overlap of isotopic niche spaces of puye in upper and middle sections of both Valdivia and Bueno rivers 20 . Predictive analyses did not associate any of the fish captured in Valdivia and Bueno river systems with estuarine elemental signatures suggesting restriction of their life-histories to freshwater habitats possibly distinct from estuarine populations.…”
Section: Discussionsupporting
confidence: 90%
“…To date, however, no estuarine resident populations have been reported. This finding is corroborated by Manosalva et al 20 who reported that isotopic niches of estuarine and freshwater populations of puye in the Imperial and Maullín rivers did not overlap.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Larval fish differ in their diel feeding behaviors by species because of their biological and environmental circumstances (Rønnestad et al, 2013). The diel feeding pattern of wild, marine stage larval giant k okopu is not known; however, studies indicate a high level of feeding flexibility by larval whitebait species, including both opportunistic and selective feeding approaches depending on prey size and density and are to the point of being able to undertake completely freshwater life cycles if required (Catlin et al, 2019;David et al, 2019David et al, , 2022Manosalva et al, 2021). Similarly, studies on adult giant k okopu indicate flexibility between feeding levels between day and night, depedning on season (David & Closs, 2003;Hansen et al, 2004); however, given the relatively poor visual acuity at early stages of development, larvae in this study may in fact benefit from the increased level of natural light intensity at the Midday and Afternoon feeding events, leading to greater capture success and therefore gut fullness (Fiksen & Jørgensen, 2011).…”
Section: Discussionmentioning
confidence: 99%